HORMONAL RESPONSES OF LACTATING DAIRY COWS TO TREATMENT WITH A PROGESTERONE INTRAVAGINAL DEVICE WITH OR WITHOUT ESTRADIOL - Prabowo P Putro (Jurnal Sain Veteriner, 2000)
The objective of this study was to evaluate the effect of progesterone supplementation through an intravaginal device on plasma progesterone and estradiol-17(3 profiles in lactating dairy cows. Eight lactating Friesian cows, between 3 and 5 years, in the luteal phase of a normal estrous cycle were used In the treated group A (n = 4), a CIDR intravaginal implant contains 1.9 gram progesterone, was inserted into the vagina of each cow at day 8 of the study and removed 9 days later. In the group B (n = 4), a CIDR combined with a 10 mg estradiol benzoate capsule was inserted into the vagina as in the group A Blood samples were taken daily for progesterone and estradiol-17(5 assays. Plasma concentrations of progesterone increased rapidly following the CIDR insertion, reached maximum at day 9 of insertion (6.28 ± 0.26 ng/ml and 5.62 + 0.16 ng/ml, respectively, P < 005), and then dropped abruptly after CIDR removal. Two days after the CIDR insertion, the plasma progesterone increased more rapidly in the group A than in the group B, and were significantly higher between days 11 and 17 of the study, but lower between days 20 (estrus) and 22 of the study (P < 0.05). The progesterone levels reached to basal levels within 3 days following the CIDR removal (0.64 + 0.12 ng/ml and 029 + 0.16 ng/ml, respectively, P < 0.05), when the cows were showing estrous behavior. The declines in the mean plasma concentrations of progesterone after the CIDR removal in the both treated groups were linear (R2 = 0.814 and 0 798, the rate of decline were 1.36 ng/ml/day and 1.29 ng/ml/day, respectively). Thereafter, the mean progesterone concentrations elevated steadily after the induced estrus. The plasma concentrations of estradiol-17(3 in the both treated groups also showed relatively the same pattern. They declined regularly in the luteal phase, increased slowly by the follicular phase, and reached maximum levels at estrus, 3.08 + 0.12 and 338 ±0.16 pg/ml (P < 0.05), respectively. The concentrations of estradiol-17(3 between days 6 and 9, days 20 (estrus) and 21 of the study in the group A were significantly lower than those in the group B (P < 0.05). The insertion of estradiol benzoate capsule significantly increased the plasma concentrations of estradiol-17(3. At the same time, the increase of plasma estradiol-17£ concentrations was followed by the decline of plasma progesterone levels. In conclusion, CIDR is a useful agent for continuous delivery of progesterone to enable estrus synchronization in lactating dairy cows. Its combination with estradiol benzoate resulted in a more marked decline in the plasma concentration of progesterone and more synchronous estrus following its removal than that of CIDR alone.